Knowledge of Play: A Precursor for Rethinking Sports Gambling Among Young Africans - Adebisi, Tunde (Critical Gambling Studies)

(untitled) (University of Alberta Library, 2023)
The degree of involvement in sports gambling activities differs among individuals, in terms of knowledge of the sport they gamble on, and betting dynamics. These sorts of differences have created distinct classes of bettors within the youth gambling population, where the lower strata consult members of the highest stratum to maximise gambling success. This article suggests that, within what is known as a youth gambling population, a community of gamblers exists. This demonstrates the necessity to avoid or mitigate the tendency to treat the youth gambling population as a unified whole. The article also articulates important dynamics of sports gambling culture among young people and explains how the activity is perceived and encouraged among/within a gambling community.